A 20-Year Antifungal Susceptibility Surveillance (From 1999 to 2019) for Aspergillus spp. and Proposed Epidemiological Cutoff Values for Aspergillus fumigatus and Aspergillus flavus: A Study in a Tertiary Hospital in China - Yang, Xinyu; Chen, Wei; Liang, Tianyu; Tan, JingWen; Liu, Weixia; Sun, Yi; Wang, Qian; Xu, Hui; Li, Lijuan; Zhou, Yabin; Wang, Qiqi; Wan, Zhe; et al. (Frontiers in Microbiology, 2021)
The emergence of resistant Aspergillus spp. is increasing worldwide. Long-term susceptibility surveillance for clinically isolated Aspergillus spp. strains is warranted for understanding the dynamic change in susceptibility and monitoring the emergence of resistance. Additionally, neither clinical breakpoints (CBPs) nor epidemiological cutoff values (ECVs) for Aspergillus spp. in China have been established. In this study, we performed a 20-year antifungal susceptibility surveillance for 706 isolates of Aspergillus spp. in a clinical laboratory at Peking University First Hospital from 1999 to 2019, and in vitro antifungal susceptibility to triazoles, caspofungin, and amphotericin B was determined by the Clinical and Laboratory Standards Institute (CLSI) broth microdilution method. It was observed that Aspergillus fumigatus was the most common species, followed by Aspergillus flavus and Aspergillus terreus. Forty isolates (5.7%), including A. fumigatus, A. flavus, A. terreus, Aspergillus niger, and Aspergillus nidulans, were classified as non-wild-type (non-WT). Importantly, multidrug resistance was observed among A. flavus, A. terrus, and A. niger isolates. Cyp51A mutations were characterized for 19 non-WT A. fumigatus isolates and TR34/L98H/S297T/F495I was the most prevalent mutation during the 20-year surveillance period. The overall resistance trend of A. fumigatus increased over 20 years in China. Furthermore, based on ECV establishment principles, proposed ECVs for A. fumigatus and A. flavus were established using gathered minimum inhibitory concentration (MIC)/minimal effective concentration (MEC) data. Consequently, all the proposed ECVs were identical to the CLSI ECVs, with the exception of itraconazole against A. flavus, resulting in a decrease in the non-WT rate from 6.0% to 0.6%.